Behavioral assessment of well-being in the naïve laboratory ferret (Mustela putorius furo) - Molly J. Goodfellow; Lorena E. Hong; Boris Piskoun; Julie L. Proctor; Jody C. Cantu; Gary Fiskum (Scientific Reports)
Abstract Domestic ferrets (Mustela putorius furo) are an emerging model species in biomedical research. While behavioral studies are a critical translational tool for evaluating neurologic function in disease models and toxicology studies, there is a lack of ferret-specific behavioral assays and corresponding data on baseline behavior. Play behavior is a promising target for evaluation of psychological well-being, particularly because ferrets engage in solitary and social play well into adulthood. Therefore, in this study, an ethogram of behaviors associated with play, elevated mood, and environmental interaction was developed and applied in experimentally naïve juvenile and young adult male laboratory ferrets (3 and 6 months of age, respectively). Total play/positive affect behavior was significantly greater in adults relative to juveniles, mostly due to increased dook vocalizations. Juveniles also took significantly longer to first exit into the behavior suite than adults. This may be linked to contextual habituation or a developmentally associated shift in anxiety-like behavior. While the frequency of total environmental interaction did not differ by age, juveniles demonstrated increased exploration of objects whereas young adults engaged in more climbing onto/into objects. Overall, this study provides a simple and efficient method to assess psychological well-being and environmental exploration in both juvenile and young adult laboratory ferrets. Future studies are needed to determine the sensitivity of these measures to neurologic injury or disease.